2022
DOI: 10.1186/s12966-022-01342-9
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and behavioural factors of adherence to the no-screen guideline for toddlers among parents from the French nationwide Elfe birth cohort

Abstract: Background Excessive screen time in infancy and childhood has been associated with consequences on children’s development and health. International guidelines call for no screen time before age 2 years, whereas in France, the most prominent guidelines recommend no screen before age 3 years. However, data are lacking on parental adherence to the no-screen guideline for toddlers and factors of adherence in France. Using data from the French nationwide Elfe birth cohort, we estimated adherence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…More broadly, in underlining the role of parental socioeconomic status in the association between screen viewing and drawing score, our findings are consistent with previous results on screen viewing and cognitive development: the context created by parents around screen viewing may better determine cognitive development outcomes 4 , 6 . This refers to parental behaviours largely dependent on parental socioeconomic status, specifically cultural capital: parents’ knowledge about the risks associated with screen viewing in childhood, their personal engagement in guiding their child’s activities and their own cultural practices or leisure activities may determine the ways in which they engage their child in screen viewing 17 . Moreover, when stratifying analyses on maternal educational level, we found that the negative association between total screen time at 3.5 years and drawing score remained only among girls whose mother had higher educational attainment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, in underlining the role of parental socioeconomic status in the association between screen viewing and drawing score, our findings are consistent with previous results on screen viewing and cognitive development: the context created by parents around screen viewing may better determine cognitive development outcomes 4 , 6 . This refers to parental behaviours largely dependent on parental socioeconomic status, specifically cultural capital: parents’ knowledge about the risks associated with screen viewing in childhood, their personal engagement in guiding their child’s activities and their own cultural practices or leisure activities may determine the ways in which they engage their child in screen viewing 17 . Moreover, when stratifying analyses on maternal educational level, we found that the negative association between total screen time at 3.5 years and drawing score remained only among girls whose mother had higher educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Our first hypothesis is that the relationship between screen viewing and the Draw-a-Person test score can be explained, partly or fully, by households’ socioeconomic status. Indeed, a negative association between parents’ educational level, income and children’s screen viewing has been widely documented 17 20 . On the other hand, as socioeconomic status is associated with children’s cognitive functioning 21 , 22 , we expect that children from households with lower socioeconomic status have poorer drawing abilities.…”
Section: Introductionmentioning
confidence: 99%
“…These include demographic, home environment and parenting factors. A number of parent (e.g., parent education) and child (e.g., age, number and ages of siblings) demographic factors have been linked with young children's screen use (Chandra et al, 2016;Corkin et al, 2021;Duch et al, 2013;Goh et al, 2016;Hoyos Cillero & Jago, 2010;Paudel, Jancey, Subedi, & Leavy, 2017;Poncet et al, 2022;Tooth et al, 2019;Yu & Baxter, 2015), however, these are variables which are not easily modifiable, and while they may help in identifying children at risk of high or problematic screen use they have limited utility in intervention design. Compared to research with older children and adolescents, there is relatively limited information on factors associated with young children's screen use beyond demographics (Elias & Sulkin, 2019;Paudel et al, 2017) and modifiable factors remain to be clearly described.…”
Section: Factors Associated With Young Children's Screen Usementioning
confidence: 99%